Analisis Faktor Minat Belajar Murid dalam Pembelajaran Al-Qur’an di TPQ Al-Ikhlas Surau Cubadak Tilatang Kamang Agam - Rapisa Putri Ayu; Alimir (ARZUSIN, 2026)
Although learning interest is an important factor determining success in Qur’an learning, studies specifically analyzing the internal and external factors that influence students’ learning interest in non-formal Qur’anic educational institutions remain limited. This study aims to analyze the factors influencing students’ learning interest in Qur’an learning at TPQ Al-Ikhlas Surau Cubadak, Tilatang Kamang, Agam Regency. This study employed a qualitative approach with a case study design. The research participants consisted of the head of the TPQ, teachers, Level II students, and students’ parents, who were selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The results showed that students’ learning interest was influenced by internal factors, including attention, enjoyment, concentration, awareness, and willingness to learn, as well as external factors comprising teacher competence, learning methods, parental support, the learning environment, learning facilities, and gadget use. These findings extend the application of the concepts of learning interest and Self-Determination Theory to the context of Qur’an learning in non-formal educational institutions. This study emphasizes the importance of collaboration among teachers, parents, and TPQ administrators in creating a conducive learning environment to enhance students’ learning interest. Theoretically, this study contributes to the development of Islamic education research, while practically, its findings can serve as a basis for TPQ administrators in designing Qur’an learning that is more engaging, supportive, and responsive to students’ needs.